2013
DOI: 10.1590/s0036-46652013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis in children attending a Public Health Service Pneumology Unit in Paraná State, Brazil

Abstract: SUMMARYThe enzyme-linked immunosorbent assay (ELISA) is the most widely used tool to detect anti-Toxocara IgG antibodies for both serodiagnostic and seroepidemiological surveys on human toxocariasis. In the last eight years a high prevalence of toxocariasis (32.2-56.0%) has been reported in children attending public health units from municipalities in the state of Paraná, Brazil. Therefore, the aim of this work was to compare the frequency found among the general child population with that of children attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(57 reference statements)
1
11
0
4
Order By: Relevance
“…Serological findings (seroprevalence of 1.6-14.5%) indicate that human infection with T. canis also occurs in Italy, with highest values in young subjects, adult epileptics, Strongyloides stercoralis-infected patients, and outdoors or soil related workers [42][43][44]. It is worthy of note that the presence of pets at home is not correlated with seroprevalence [45], while the most important factor that increases the seropositivity in human beings is represented by the habit of frequenting public soils contaminated with a high load of infectious Toxocara eggs [46]. These observations highlight that Toxocara infections in people mainly originate through a saprozoonotic route, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Serological findings (seroprevalence of 1.6-14.5%) indicate that human infection with T. canis also occurs in Italy, with highest values in young subjects, adult epileptics, Strongyloides stercoralis-infected patients, and outdoors or soil related workers [42][43][44]. It is worthy of note that the presence of pets at home is not correlated with seroprevalence [45], while the most important factor that increases the seropositivity in human beings is represented by the habit of frequenting public soils contaminated with a high load of infectious Toxocara eggs [46]. These observations highlight that Toxocara infections in people mainly originate through a saprozoonotic route, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…10,27,[30][31][32]36,40 In all of these studies, a higher proportion of patients with asthma was found among those infected with Toxocara, which lends this infection greater relevance in terms of public health.…”
Section: Resultsmentioning
confidence: 93%
“…10,[24][25][26][27][28][29][31][32][33][34][36][37][38][39][40][41][42][43][44] One study did not describe the diagnostic methodology applied. 35 As T. canis and T. cati cannot be distinguished serologically, we identified the study population as having toxocariasis.…”
Section: Resultsmentioning
confidence: 99%
“…As for STH infections, human infections with the cosmopolitan helminth Toxocara, have been associated with allergy in humans . Toxocara is a zoonotic infection that is unable to develop to adulthood in the human host.…”
Section: Helminths and Allergy In Brazilmentioning
confidence: 99%
“…70 As for STH infections, human infections with the cosmopolitan helminth Toxocara, have been associated with allergy in humans. [71][72][73][74][75] Toxocara is a zoonotic infection that is unable to develop to adulthood in the human host. The infection is caused by contact with an environment contaminated with faeces from dogs infected with Toxocara canis and cats with Toxocara cati.…”
Section: >14%mentioning
confidence: 99%